2015
DOI: 10.1515/acpa-2015-0010
|View full text |Cite|
|
Sign up to set email alerts
|

Palynostratigraphy, palynofacies and depositional environment of a lignite-bearing succession at Surkha Mine, Cambay Basin, north-western India

Abstract: The paper reports palynology and palynofacies studies of lignite-bearing sediments exposed in an opencast mine succession at Surkha, Bhavnagar District, in the coastal region of Gujarat, India. The study examined the relationships between the palynoflora, sedimentary organic matter and environment at the time of deposition of lignite and associated sediments. Based on dinoflagellate cyst biostratigraphy, the sedimentary succession is dated as early Eocene (Ypresian). Palynofacies studies helped reveal the pala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The early Eocene flora is well documented from the palynological analysis of coal-bearing successions across India (Monga et al 2015, Prasad et al 2009, Samant & Phadare 1997. The pollen flora suggests a setting with a perhumid climate, and tall, dense, closed-canopy rain forests of modern aspect.…”
Section: Indian Climate and Flora Prior To Collision With Asiamentioning
confidence: 99%
“…The early Eocene flora is well documented from the palynological analysis of coal-bearing successions across India (Monga et al 2015, Prasad et al 2009, Samant & Phadare 1997. The pollen flora suggests a setting with a perhumid climate, and tall, dense, closed-canopy rain forests of modern aspect.…”
Section: Indian Climate and Flora Prior To Collision With Asiamentioning
confidence: 99%
“…Brownlowia may also occur in tidally influenced freshwater swamps along the coastal plain [ Morley , ; Tomlinson , ]. In addition, several single occurrences of palm tree‐type pollens such as Nypa and the extinct Neocouperipollis representing palms from the coastal environment, and extending toward tidally influenced rivers and freshwaters swamps further inland [ Giesen et al ., ; Monga et al ., ], are observed along the entire section (Table S3).…”
Section: Palynologymentioning
confidence: 99%
“…Thyriothecia with a papillate ostiole and a lower wall are characteristic of Trichothyriaceae. Anisotomous At present, T. setifer (Monga et al, 2015), from the early Eocene (56-47.8 Ma), represents the oldest convincing evidence of the clade including Microthyriales and Venturiales.…”
Section: Case Studies: Interpreting Characters Of Fossils-a Dispersedmentioning
confidence: 98%
“…Analysis of fossils-We selected three fossils reported as thyriothecial from the literature that were well enough illustrated to be coded for morphology. These include the oldest dispersed thyriothecium-like structure (Mishra et al, 2018), a dispersed Lichenopeltella-like form (Monga et al, 2015) for which cell patterns could be analyzed, and Asterina eocenica found on a leaf associated with mycelium (Dilcher, 1965). As for extant taxa, we coded character states from the illustrations (Appendix S4).…”
Section: Analysis Of Morphological Characters-we Performed Maximum LImentioning
confidence: 99%
See 1 more Smart Citation